Transformations in the labor market and the Brazilian experience after labor reform of 2017 (Research, Society and Development, 2018)
The reconfiguration of capitalism, in a context of strengthening its financial dimension and progress towards greater flexibility in labor relations and regulation, has led to significant changes in the organization of work and the dynamics of the labor market. In this sense, the article seeks to present some reflections on the impacts of the transformations of contemporary capitalism to the world of work, bringing to the debate the recent Brazilian experience after de Labor Reform of 2017. Some data will be explored to show the flow of hiring and dismissing of workers. The data are available in the General Register of Employed and Unemployed - CAGED of the Ministry of Labor. The main conclusion is that the implemented Labor Reform was not able to provide a recovery of the labor market. It is necessary to point out that the solution to the problems of employment and income is linked to the increase in economic activity and its association with regulatory mechanisms that protect and do not withdraw workers' rights.